Scan QR code or get instant email to install app

Skip to content
#
Simplify the given expression:

9(9 − 10r) + (−8 − 2r) =

### Related Information

Question:

9(9 − 10r) + (−8 − 2r) =

`_________`

.
A
73 − 92r

explanation

To simplify the given expression, let's distribute the 9 to the terms inside the parentheses:

9(9 - 10r) + (-8 - 2r)

= 81 - 90r + (-8 - 2r)

Next, we can combine like terms. The terms with "r" are -90r and -2r. Combining them gives us -92r.

= 81 - 92r - 8

Finally, we can combine the constant terms 81 and -8:

= 73 - 92r

Therefore, the simplified expression is 73 - 92r.

Take more free practice tests for other GED topics with our ged online now!

Comments